The interaction between relevant-set based operators and a topic–predicate dimension - Anna Szeteli; Gábor Alberti (LingBaW)
Hungarian relevant-set based operators, such as universally quantified noun-phrases and the also-quantifier, signal a logico-pragmatic relation between their explicit meaning and a broader implicit set of relevant participants which property can be mentioned as “double referentiality” of the operator. Furthermore, they indicate the new or correcting information in a topic–predicate dimension which belongs to the broader world of the discourse. Our research aims to identify the differences by investigating the suprasegmental features of each-quantifiers and also-quantifiers on the Hungarian left-periphery indicating the two functions in the topic–predicate dimension. Short sentences in which quantifiers functioning either as the main (new/correcting) information or as a topic (anchor of relevant information) were read by 41 non-linguist native Hungarian subjects. The pitch, intensity and duration properties were analyzed by Praat. On the basis of paired t‑tests of the data, it can be stated that a two-dimension model of information structure is required to capture the phenomenon.